Technical Feasibility of Mechanical Planting of Sunflower Seeds - Singh, Sukhbir; Sharma, D N (Journal of Agricultural Engineering, 2009)
In Haryana state, broadcasting and dibbling on ridges are the most commonly used conventional practices for sunflower sowing which are very much time consuming and laborious operations. Four different types of rollers were fabricated and evaluated under laboratory condition in terms of quantity of seed metered, volumetric cell fill, seed germination and seed damage at three seed column height in hopper and four different speeds. Uniformly shaped triangular small cell type roller (R4) gave optimum performance between 17-40 rpm of its operation. A prototype of single row manually operated sunflower planter was developed by using optimum roller (R4) and evaluated at University and farmers’ field. The average field capacity of the planter was 0.1030 ha/h. The seed germination was 22.66 plants/mÂ² and 14.66 plants/mÂ² for MYCO-8 & HS-1 varieties, respectively. The sowing of sunflower by planter resulted in net saving of 57.16 man-hours and 1.50 tractor-hours per hectare over broadcasting and 57.91 man-hours and 2.25 tractor-hours per hectare over dibbling method.